Creativity as a Bridge: How Narcissism Affects Lecturer Performance - Ridolof W. Batilmurik; Robert M. Noach; Bernad A. W. Bowakh; David Latupeirissa; Faustina P. Kemba (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines how narcisim influences job performance through creativity as a mediator. A survey of 96 lecturers in Indonesian universities used established measures for narcisim, creativity, and job performance. Statistical analyses assessed validity, reliability, and a mediation model to understand the impact of narcisim on performance through creativity. Findings: Narcissistic traits lowered creativity, which reduced job performance. However, fostering creativity can mitigate some of these negative effects, highlighting its importance for improving lecturer performance. Practical Implications: To manage the impact of narcissism on lecturer performance, organizations should focus on fostering creativity through training programs, innovation-supportive policies, and selection and evaluation processes that emphasize creativity. Additionally, psychological support for lecturers with high levels of narcissism can help mitigate negative effects and enhance overall performance. Originality: The study provides new insights for developing strategies that can enhance lecturer performance through the management of narcissistic traits and the promotion of creativity.